CBS News Monthly Poll #1, October 2008 ([Verlag nicht ermittelbar], 2010)
This special topic poll is part of a continuing series of monthly surveys that solicits public opinion on the presidency and on a range of other political and social issues. In this poll, fielded October 3-5, 2008, respondents were asked whether they approved of the way George W. Bush was handling the presidency, their opinion of the condition of the national economy, and whether it was getting better or worse. Those who were registered to vote were asked how much attention they were paying to the 2008 presidential campaign, their opinions of the presidential and vice presidential candidates and their abilities, the degree of their support for the candidates, whether the presidential candidates choice for vice president would influence their vote, whether they had voted in a Democratic or Republican primary or caucus that year, and the likelihood that they would vote in the general election and for whom. Respondents were also asked whether they watched or listened to the vice presidential debate held October 2, 2008, who they thought did the best job, whether their opinions of the vice presidential candidates changed as a result of the debate, the likelihood that they would watch the second presidential debate, and their prediction on who would win the presidential debate. Several questions addressed the economic crisis and included questions that asked whether respondents approved of the way Congress was handling its job, whether they approved of the way George W. Bush and Congress was handling the crisis, whether they approved of the federal government providing money to financial institutions, whether the federal government should provide financial assistance to financially troubled homeowners, whether they approved of the bailout plan passed by Congress, and who they thought would benefit from the money used in the bailout plan. Other topics addressed whether the respondent knew of anyone who supported Barack Obama mainly because of his race, and which sport the they followed the most. Demographic variables include sex, age, race, education level, marital status, household income, political party affiliation, political philosophy, voter registration status and participation history, length of time at current residence, whether there were children under the age of 18 living with the respondent, labor union membership, religious preference, and whether respondents considered themselves to be a born-again Christian.